Sympathetic and angiotensinergic activity in spontaneously hypertensive rats treated with 3-amino-1,2,4-triazole - Pontes, Roberto Braz [UNESP]; Colombari, Débora S.A. [UNESP]; De Paula, Patrícia M. [UNESP]; Colombari, Eduardo [UNESP]; Andrade, Carina A.F. [UNESP]; De Luca, Laurival A. [UNESP]; Menani, José V. [UNESP] (Elsevier, 2023)
Previous studies from our laboratory have shown that the pressor response to intracerebroventricular (icv) administered ANG II in normotensive rats or spontaneously hypertensive rats (SHRs) is attenuated by increased central H2O2 concentration, produced either by direct H2O2 icv injection or by increased endogenous H2O2 centrally in response to local catalase inhibition with 3-amino-1,2,4-triazole (ATZ). In the present study, we evaluated the effects of ATZ administered peripherally on arterial pressure and sympathetic and angiotensinergic activity in SHRs. Male SHRs weighing 280–330 g were used. Mean arterial pressure (MAP) and heart rate (HR) were recorded in conscious freely moving SHRs. Acute intravenous injection of ATZ (300 mg/kg of body weight) did not modify MAP and HR during the next 4 h, however, the treatment with ATZ (300 mg/kg of body weight twice per day) for 3 days reduced MAP (144 ± 6, vs. saline, 183 ± 13 mmHg), without changing HR. Intravenous hexamethonium (ganglionic blocker) produced a smaller decrease in MAP 4 h after ATZ (−25 ± 3, vs saline −38 ± 4 mmHg). Losartan (angiotensinergic AT1 receptor blocker) produced a significant depressor response 4 h after ATZ (−22 ± 4, vs. saline: −2 ± 4 mmHg) and in 3-day ATZ treated SHRs (−25 ± 5, vs. saline: −9 ± 4 mmHg). The results suggest that the treatment with ATZ reduces sympathetic activity in SHRs and simultaneously increases angiotensinergic activity.
Keywords: Arterial pressure; Catalase; H2O2; Hypertension